Optical force microscopy: combining light with atomic force microscopy for nanomaterial identification - Jahan Nusrat; Wang Hanwei; Zhao Shensheng; Dutta Arkajit; Huang Hsuan-Kai; Zhao Yang; Chen Yun-Sheng (Nanophotonics, 2019)
Scanning probe techniques have evolved significantly in recent years to detect surface morphology of materials down to subnanometer resolution, but without revealing spectroscopic information. In this review, we discuss recent advances in scanning probe techniques that capitalize on light-induced forces for studying nanomaterials down to molecular specificities with nanometer spatial resolution.